Effectiveness of structured teaching programme on knowledge regarding rubella vaccine among parents of children, 1-12 year - Goswami, Chirag Giri; Kumawat, Shalini Raj; Pandya, Hardik (International Journal Of Community Medicine And Public Health, 2021)
Background: Rubella also known as German measles is a mild viral disease characterized by mild fever and maculopapular rash. During 2000-2018, measles vaccination prevented an estimated 23.2 million deaths. Routine measles vaccination for children combined with mass immunization campaigns in countries with high case and death rates, are key public health strategies to reduce global measles deaths. The aim of the study is to assess the effectiveness of structured teaching programme on knowledge regarding rubella vaccine among parents of children (1-12 year). Methods: Pre experimental one group pre-test post-test design. Total 60 parents were taken who have children (1-12 years); purposive sampling technique was used to select the parents. A structured knowledge questionnaire was prepared by the investigator. Informed consent was taken from each participant prior to data collection and Descriptive and inferential statistics i.e., frequency, percentage, paired’ test, chi-square test was used for analysis. Results: Pre-test knowledge score of parents regarding rubella vaccine revealed that 53.33% parents had inadequate knowledge, and 46.66% parents had moderately knowledge. After structured teaching programme, the posttest knowledge scores of parents shows that 13.33% parents had adequate knowledge, 83.33% parents had moderately adequate knowledge and 3.33% have inadequate knowledge. Conclusions: The structured teaching programme (STP) through flash cards, charts and roller board etc. found to be very effective in improving the knowledge among parents who have children (1-12 year) on rubella vaccine.